If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + n + 5 + 6 = 5 + 4n + -4 Reorder the terms: -13 + 5 + 6 + n = 5 + 4n + -4 Combine like terms: -13 + 5 = -8 -8 + 6 + n = 5 + 4n + -4 Combine like terms: -8 + 6 = -2 -2 + n = 5 + 4n + -4 Reorder the terms: -2 + n = 5 + -4 + 4n Combine like terms: 5 + -4 = 1 -2 + n = 1 + 4n Solving -2 + n = 1 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -2 + n + -4n = 1 + 4n + -4n Combine like terms: n + -4n = -3n -2 + -3n = 1 + 4n + -4n Combine like terms: 4n + -4n = 0 -2 + -3n = 1 + 0 -2 + -3n = 1 Add '2' to each side of the equation. -2 + 2 + -3n = 1 + 2 Combine like terms: -2 + 2 = 0 0 + -3n = 1 + 2 -3n = 1 + 2 Combine like terms: 1 + 2 = 3 -3n = 3 Divide each side by '-3'. n = -1 Simplifying n = -1
| -15=-3+3u | | ((9)(9))+((16)(16))=((25)(25)) | | -5x-8-7=20 | | 8m-28=-18 | | -xy+3y+10x= | | 20=6-2 | | 8x-6=8x-3 | | 5e^5t=8e^4t | | -7p+2p=15 | | 4p-p^2= | | 2x-21=5x+75 | | -6v=-30 | | 3n-15=7n+n | | -90+12x=153+3x | | (x+5)=12 | | 2k+2k=-16 | | -12-4b=4-2b | | ((36)(36))+((77)(77))=((85)(85)) | | -(4,3)y-(6,5)=-(1,2) | | 83+x+109=180 | | 4r+8+5=-15-3r | | -3=6x+7 | | -8=-6x-1-x | | 2x+4+3x+8=90 | | x^5(x^2+3x-2)=0 | | 5x+3(2x+4)=2(5x+6) | | (a-3)(a-2)=4 | | 1-3x=3x+1 | | .7(.9x-2)=3.21x-.75 | | 5(x-1)=5x+5 | | 3-2x+7+y+x= | | 6a(b+2c)= |